Current Practical Concepts for Using Rib in Secondary Rhinoplasty - Robotti, Enrico; Penna, Waldemar Brandao (Facial Plastic Surgery, 2019)
Rhinoplasty is universally considered as the most demanding procedure in facial plastic surgery. Secondary rhinoplasty is its crown jewel, even more complex, and likewise highly fascinating. The evolution of thought and practice in rhinoplasty in the last decades has been quick and steady, progressively acknowledging the importance of maintaining structure in primary rhinoplasty and rebuilding structure in secondary procedures. No longer is the paradigm to achieve a small, thin, and pointy nose, but rather a well-proportioned nose which looks natural, albeit elegant and breathing well. Rib is an essential tool in many secondary procedures, and thus some important concepts have to be well understood and some finesse points mastered. This will provide an elegant reconstruction, identical if possible, or at least not far apart, to what could be achieved by a well-executed primary rhinoplasty, while avoiding the feared luck of a bulky nose stuffed with grafts. These guiding concepts and specific nuances regarding harvesting rib and working with it are the scope and contents of this article.
Keywords: graft; rhinoplasty; rib cartilage